Molecular and Biochemical Characterization of a Cytokinin Oxidase from Maize - Bilyeu, Kristin D. (American Society of Plant Physiologists, 2001)
It is generally accepted that cytokinin oxidases, which oxidatively remove cytokinin side chains to produce adenine and the corresponding isopentenyl aldehyde, play a major role in regulating cytokinin levels in planta. Partially purified fractions of cytokinin oxidase from various species have been studied for many years, but have yet to clearly reveal the properties of the enzyme or to define its biological significance. Details of the genomic organization of the recently isolated maize (Zea mays) cytokinin oxidase gene (ckx1) and some of its Arabidopsis homologs are now presented. Expression of an intronless ckx1 in Pichia pastoris allowed production of large amounts of recombinant cytokinin oxidase and facilitated detailed kinetic and cofactor analysis and comparison with the native enzyme. The enzyme is a flavoprotein containing covalently bound flavin adenine dinucleotide, but no detectable heavy metals. Expression of the oxidase in maize tissues is described.